Analisis Strategi Global Marketing Disney Plus di Korea Selatan: Studi Kasus K-drama “Moving” Tahun 2023 - Setyawan, Stephanie Sheren; Rasyidah, Resa (Widya Manajemen, 2025)
This research analyzes Disney+'s international marketing strategy in expanding its market reach through utilizing South Korean popular culture. In entering the South Korean market, Disney+ adopted an adaptation strategy by collaborating with local partners to produce content that resonates with local culture and preferences. One example of the success of this strategy is the K-drama series Moving, which was adapted from Webtoon and won 6 awards at the Asia Contents Awards & Global OTT Awards 2023. The series tells the story of a group of intelligence agents who try to protect their children from potential exploitation by the government. This research uses a descriptive qualitative method with data collection techniques through literature study, content analysis, and observation of Disney+ marketing strategies in the South Korean market. The data will be analyzed using the 7P marketing mix concept to examine how Disney+ integrates local content in its international marketing strategy. The results show that content adaptation and cooperation with local partners are the keys to Disney+'s success in building competitiveness and increasing the number of subscribers in the South Korean market.